An Exploration To Determine Essential Requirements For Smart Home Application - Ismail, Fazilah; Ahmad, Sabrina; Hashim, Ummi Rabaah (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The revolution of Internet of Things (IoT) will be able to revive the way people use the technology for a greater benefit. As we are embarking towards the golden age of technology, smart home application is gaining popularity as it adds convenience, comfort and peace of mind. There are variety of smart home applications worldwide which has diverse functionality with different perspectives and embedded assumptions. These scenario leads to uncertainty among the developers and leads to unnecessary effort to elicit requirements every time new application wants to be developed. Therefore, this paper presents an exploration to determine essential requirements for smart home application based on end user needs. An empirical investigation based on survey technique was conducted to determine essential requirements for smart home application. A case study of residents in Satellite City of Muadzam Shah, Pahang was conducted. The analysis was done by using T-Test and One Way Analysis of Variance (ANOVA). The results show that the respondents agreed the essential requirements for smart home application are Time Needs, Simplicity Needs, Security and Safety Needs and Mobility Needs.